Introduction to the special issue on “Brazilian fossiliferous sites with paleobiological importance” - Rodrigo Horodyski; Hermínio Ismael de Araújo Júnior (Journal of the Geological Survey of Brazil)
To enhance our understanding of Brazilian paleontological heritage, we have launched the special edition titled “Brazilian Fossiliferous Sites with Paleobiological Importance”. A total of seven manuscripts have been accepted and published in Vol. 7 No. SI2 (2024). Recognizing our fossil heritage is essential for the scientific and cultural advancement of Brazil. We strongly encourage paleontologists to continuously publish papers on our rich fossiliferous deposits.